THE INFLUENCE OF SMART FLANEL BOARD MEDIA TOWARD THE ABILITY OF SUMMATION NUMERACY CHILLDREN WITH INTELLECTUAL DISABILITY - Ni’amul Ludfi, M Kholid; ., Sulthoni (Jurnal Penelitian dan Pengembangan Pendidikan Luar Biasa, 2016)
The subject in this research who have difficulty on summation nemeracy 1-10. The purpose of this research are to describe: (1) Summation numeracy for 3th grade chilldren with intellectual disability in baseline conditions; (2) Summation numeracy for 3th grade chilldren with intellectual disability after the intervention condition; (3) The influence of smart flanel board media toward summation numeracy for 3th grade chilldren with intellectual disability. This research is an Single Subject Research (SSR) method with A-B-A design. The results of this research is smart flanel board media has an influence toward count numeracy for 3th grade chilldren with intellectual disability.